Ghana Youth Employment Program Inventory - Avura, Francis Babongte; Ulzen-Appiah, Ato (World Bank, Washington, DC, 2017)
This youth employment inventory has been compiled to improve the evidence base for making decisions about how to address the problem of youth unemployment or youth who are not in education and not participating in the labor market in Ghana. Policy makers who are considering measures to help young people make the transition into the labor market and obtain decent work are hampered by a lack of information on the various options, the effectiveness of the options in different situations, and options that have been tried and failed among different youth profiles. To guide public policy and inform private efforts, more evidence is needed about the effectiveness of different initiatives and approaches in promoting youth employment and fostering a smooth transition from education and training to work. This study takes a modest step in this direction by mapping youth employment initiatives in Ghana. The government of Ghana has undertaken many initiatives to address the youth unemployment challenges. At the same time, many private sector organizations, some for private entities and others that are nonprofit efforts, have undertaken training programs to contribute to and improve the labor force in Ghana. The key focus of youth employment initiatives in Ghana is skills development and training, entrepreneurial training, apprenticeship, employment services, and direct employment. A total of 40 youth employment programs have been analyzed for this report. Of these, 18 are in the public sector and are implemented by government ministries, departments, and agencies (MDAs). The other 22 interventions are implemented by the private sector, which includes corporate entities, nongovernmental organizations (NGOs), and civil society organizations (CSOs). The existing programs are highly concentrated around skills development, training, and entrepreneurship training. Apprenticeship programs are more common in public sector programs, where over a third of programs offer apprenticeships.